Effect of heavy impurities on the dynamics of supercooled liquids - Chakrabarty, Saurish (2021)
We study the effect of heavy impurities on the dynamics of supercooled liquids. In a supercooled liquid, when we make a small fraction of particles heavier, they exhibit slower dynamics than the original particles and also make the overall system slower. If one looks at the overlap correlation function to quantify dynamics in the system, it has different behaviors for the heavy and the light particles. In particular, at the relaxation time of the overall system, the degree of relaxation achieved by the heavier particles is lesser, on average, than that achieved by the lighter particles. This difference in relaxation, however, goes down drastically as a crossover temperature, T0, is crossed. Below this crossover temperature, particles in the system have similar relaxation times irrespective of their masses. This crossover temperature depends on the fraction of the heavy particles and their masses. Next, we isolate the effect of mass heterogeneity on the dynamics of supercooled liquids and find that its effect increases monotonically with temperature. We also see that the development of dynamical heterogeneity with decreasing temperature is less dramatic for the system with impurities than for the pure system. Finally, the introduction of heavy impurities can be seen as a way of reducing the kinetic fragility of a supercooled liquid.